Investigations on Zinc Isotope Fractionation in Breast Cancer Tissue Using in vitro Cell Culture Uptake-Efflux Experiments - Schilling, Kathrin; Harris, Adrian L.; Halliday, Alex N.; Schofield, Christopher J.; Sheldon, Helen; Haider, Syed; Larner, Fiona (Frontiers in Medicine, 2022)
Zinc (Zn) accumulates in breast cancer tumors compared to adjacent healthy tissue. Clinical samples of breast cancer tissue show light Zn isotopic compositions (δ66Zn) relative to healthy tissue. The underlying mechanisms causing such effects are unknown. To investigate if the isotopic discrimination observed for in vivo breast cancer tissue samples can be reproduced in vitro, we report isotopic data for Zn uptake-efflux experiments using a human breast cancer cell line. MDA-MB-231 cell line was used as a model for triple receptor negative breast cancer. We determined Zn isotope fractionation for Zn cell uptake (Δ66Znuptake) and cell efflux (Δ66Znefflux) using a drip-flow reactor to enable comparison with the in vivo environment. The MDA-MB-231 cell line analyses show Zn isotopic fractionations in an opposite direction to those observed for in vivo breast cancer tissue. Uptake of isotopically heavy Zn (Δ66Znuptake = +0.23 ± 0.05‰) is consistent with transport via Zn transporters (ZIPs), which have histidine-rich binding sites. Zinc excreted during efflux is isotopically lighter than Zn taken up by the cells (Δ66Znefflux = −0.35 ± 0.06‰). The difference in Zn isotope fractionation observed between in vitro MDA-MB-231 cell line experiments and in vivo breast tissues might be due to differences in Zn transporter levels or intercellular Zn storage (endoplasmic reticulum and/or Zn specific vesicles); stromal cells, such as fibroblasts and immune cells. Although, additional experiments using other human breast cancer cell lines (e.g., MCF-7, BT-20) with varying Zn protein characteristics are required, the results highlight differences between in vitro and in vivo Zn isotope fractionation.